2004
DOI: 10.1038/ng1393
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in EFHC1 cause juvenile myoclonic epilepsy

Abstract: Juvenile myoclonic epilepsy (JME) is the most frequent cause of hereditary grand mal seizures. We previously mapped and narrowed a region associated with JME on chromosome 6p12-p11 (EJM1). Here, we describe a new gene in this region, EFHC1, which encodes a protein with an EF-hand motif. Mutation analyses identified five missense mutations in EFHC1 that cosegregated with epilepsy or EEG polyspike wave in affected members of six unrelated families with JME and did not occur in 382 control individuals. Overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
330
3
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(361 citation statements)
references
References 26 publications
16
330
3
12
Order By: Relevance
“…Consequently, voltage-gated and ligand-gated ion channels are the preeminent targets for AEDs. Indeed, when linkage studies have identified genes of unknown function as candidate epilepsy genes, the gene products have often turned out to be ion channel subunits or proteins associated in some way with ion channels (see discussion of EFHC1 34 and LGI1 35 in the sections on voltage-gated calcium and potassium channels, respectively).…”
Section: New Approaches To Identify Aed Molecular Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, voltage-gated and ligand-gated ion channels are the preeminent targets for AEDs. Indeed, when linkage studies have identified genes of unknown function as candidate epilepsy genes, the gene products have often turned out to be ion channel subunits or proteins associated in some way with ion channels (see discussion of EFHC1 34 and LGI1 35 in the sections on voltage-gated calcium and potassium channels, respectively).…”
Section: New Approaches To Identify Aed Molecular Targetsmentioning
confidence: 99%
“…89 Five mutations in EFHC1, a gene encoding a protein with an EF-hand motif, have been found in families with juvenile myoclonic epilepsy (JME). 34 This protein associates with the R-type Ca 2ϩ channel Ca v 2.3. EFHC1 increases R-type Ca 2ϩ currents, but this activity is lost when the protein bears the mutations associated with JME.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…Moreover, inherited grand mal or tonicclonic seizures can result from JME [Janz, 1959]. A recent report suggested that JME may be caused by mutations in the EFHC1 gene [Suzuki et al, 2004]. Here I will discuss the evidence supporting a role for Efhc1 in JME and detail recent analyses [Ikeda et al, 2005] that demonstrate that this protein is the mammalian orthologue of Chlamydomonas Rib72 and as such is likely an integral axonemal component [Patel-King et al, 2002;Ikeda et al, 2003] located within the protofilament ribbons [Ikeda et al, 2003] and, potentially, is also present in basal bodies/centrioles [Hinchcliffe and Linck, 1998;Keller et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Northern analysis of murine tissues demonstrated that Efhc1 expression was vastly upregulated in testis and was also prominent in lung and oviduct [Suzuki et al, 2004;Ikeda et al, 2005], which both contain large numbers of ciliated cells. In comparison, expression levels in other murine tissues including brain, heart, kidney, and spleen were low.…”
Section: Introductionmentioning
confidence: 99%
“…1991; Suzuki et al. 2004). Ultimately, further genetic, informatics and molecular experimental studies identified mutations in Myoclonin1 /EFHC1 in 6p12 as disease causing in JME (Suzuki et al.…”
Section: Introductionmentioning
confidence: 99%